You are Forgiving, So you are Human! - Primova, F. A. (European Journal of Life Safety and Stability (2660-9630), 2022)
In the current process of globalization, the issue of religious tolerance, interreligious harmony, mutual cooperation serves as one of the most important principles for the peace and development of developed and developing countries. Endurance, tolerance, tolerance, respect for different human views and actions, kindness, diligence, forgiveness, kindness, sympathy, etc., are the main virtues that distinguish us from the animal world. If this one feeling had not been given to mankind, evil, nationalism, religious and racial discrimination would have occupied the hearts of people, and we would have fallen into the swamp of barbarism. Therefore, among the human qualities, tolerance occupies a leading place, in other words, our humanity is measured by the breadth of our hearts.